Chemicals from lignocellulosic biomass: A critical comparison between biochemical, microwave and thermochemical conversion methods. Issue 14 (18th July 2021) - Yu, Iris K. M.; Chen, Huihui; Abeln, Felix; Auta, Hadiza; Fan, Jiajun; Budarin, Vitaly L.; Clark, James H.; Parsons, Sophie; Chuck, Christopher J.; Zhang, Shicheng; Luo, Gang; Tsang, Daniel C.W
Abstract: The past decades have seen an increasing interest in developing pathways to produce bio-based chemicals from lignocellulosic biomass and organic waste as renewable resources. Using biomass as a source of chemical building blocks is critical to a future sustainable chemical industry. The successful development of bio-chemicals will also have a profound impact in terms of the innovations of new polymers and materials, new solvents, and new bio-active compounds. This article provides a broad review of conventional thermal heating, microwave processing, and biochemical processing for the production of value-added bio-based chemicals. The potentially important but currently little exploited microwave-assisted processes are given particular attention and the microwave-specific, non-thermal effects are explored. The comparative merits of different approaches are evaluated from the techno-economic and environmental perspectives. The opportunities of integrated biorefineries are articulated, with the aim to actualize carbon-efficient valorization of lignocellulosic biomass and organic waste for synthesizing an array of products. Graphical abstract: UF0001